2014
DOI: 10.4049/jimmunol.1300695
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cell Motility and T Cell Activation Requires Regulation of Rho-Cofilin Signaling by the Rho-GTPase Activating Protein Myosin IXb

Abstract: Directed migration of stimulated dendritic cells (DCs) to secondary lymphoid organs and their interaction with Ag-specific T cells is a prerequisite for the induction of primary immune responses. In this article, we show that murine DCs that lack myosin IXB (Myo9b), a motorized negative regulator of RhoA signaling, exhibit increased Rho signaling activity and downstream acto-myosin contractility, and inactivation of the Rho target protein cofilin, an actin-depolymerizing factor. On a functional level, Myo9b−/−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
55
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 44 publications
4
55
0
1
Order By: Relevance
“…6A). Active RhoA (RhoA-GTP) levels, but not total RhoA, are known to be increased in mouse macrophages (1) and dendritic cells (38). We found that total RhoB levels were markedly reduced in Myo9b Ϫ/Ϫ macrophages, when compared with WT cells (Fig.…”
Section: Deletion Of Rhob Partially Rescues the Motility Defect Of Myo9bmentioning
confidence: 72%
See 1 more Smart Citation
“…6A). Active RhoA (RhoA-GTP) levels, but not total RhoA, are known to be increased in mouse macrophages (1) and dendritic cells (38). We found that total RhoB levels were markedly reduced in Myo9b Ϫ/Ϫ macrophages, when compared with WT cells (Fig.…”
Section: Deletion Of Rhob Partially Rescues the Motility Defect Of Myo9bmentioning
confidence: 72%
“…Ϫ/Ϫ Macrophages-The motorized RhoGAP Myo9b is a key negative regulator of Rho in leukocytes (1,38). We next tested whether genetic deletion of RhoB rescued the motility defect of macrophages lacking Myo9b (1).…”
Section: Deletion Of Rhob Partially Rescues the Motility Defect Of Myo9bmentioning
confidence: 99%
“…RhoGAPs rapidly convert RhoGTPases to their GDP‐bound inactive state. Although ~80 RhoGAPs are encoded by the human genome, 6 , 7 the function of RhoGAP in T cells has not been extensively investigated 8 , 9 …”
Section: Introductionmentioning
confidence: 99%
“…Myo9b-deficient macrophages fail to spread and remain in a round shape [11]. Additionally, Myo9b-depleted dendritic cells and T-cells are also defective in chemotactic migration [12,13]. It has been proposed that Myo9b acts as a single-headed myosin motor that is capable of moving along actin filaments [14,15].…”
Section: Introductionmentioning
confidence: 99%